22.2: Invited Paper: Opportunities for Multimodal Thin‐Film Transistors in Displays and Beyond. (26th August 2021) - Bestelink, Eva; De Sagazan, Olivier; Sporea, Radu A.
Abstract : Multimodal transistors (MMTs) build on previous understanding of contact‐controlled transistors. Additionally, they allow precise control of the charge injected, distinct from controlling the state of conduction of the semiconductor channel. This approach leads to interesting functionality, of benefit to displays and other large area electronic circuits. Here, we summarize the construction and functionality of the MMT and outline potential applications.